PUBLIC INTERNAL AUDIT IN ROMANIA: A REVIEW ON CHALLENGES AND IMPLICATIONS - UDRESCU LUCIA-MARIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The Public Internal Audit plays a fundamentally important role in increasing the level of transparency, accountability, and effectiveness of the management of public resources. In Romania, a number of significant changes were brought about with respect to the elaboration and implementation of models of internal audit by the country's accession to the EU and their compliance with international practices of audit. This paper aims to present an extended review regarding the public internal audit function in Romania, focusing on its legal framework, challenges, and effectiveness in general. The role of internal audit for Romanian public organizations, in enhancing governance, risk management, and internal control systems, is analyzed based on literature review and empirical research. The results thus show that, while significant progress has been made, certain limitations still prevent the full effectiveness of public internal audits in giving rise to accountability in organizations of the public sector.